Reforms, Resilience, and Global Linkages: India’s Foreign Trade Story (1991–Present) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The liberalisation of India’s economy in 1991 marked a turning point in its post-independence development trajectory. Triggered by a severe balance-of-payments crisis, the reforms dismantled a highly restrictive trade and industrial regime and introduced policies aimed at integrating India into the global economy. This paper critically examines the transformation of India’s foreign trade over the past three decades, highlighting the magnitude, composition, direction, and policy architecture of trade flows from 1991 to the present. Drawing on secondary data, policy reports, and academic research, it traces the evolution of India’s exports and imports, the structural shift from primary goods to manufactured and high-value-added services, and the progression of tariff and non-tariff measures. The findings reveal that India’s trade volume increased several-fold, services exports—particularly in information technology and IT-enabled services—emerged as a cornerstone of external earnings, and export composition diversified toward engineering goods, chemicals, and pharmaceuticals. Nevertheless, persistent challenges such as trade deficits, limited participation in global value chains, and infrastructural bottlenecks constrain India’s competitiveness in the world economy. The paper argues that while liberalisation transformed India’s external sector, trade integration remains partial and uneven, requiring renewed policy attention to trade facilitation, tariff rationalisation, logistics, and regional value-chain participation. It concludes by outlining policy lessons and directions for future research, particularly the need to study firm-level responses and India’s integration into global value-added trade.